Artistic Thinking and Societal Change - Erkkilä-Hill, Jaana (Bloomsbury, 2024)
The meaning of art has changed through centuries and even during the past decades. Some of the old meanings have kept their status quo and new ones have taken their place alongside the old and tried ones. Art has always had instrumental value: as a religious object or ritual, as a sign of wealth, as a mean to demonstrate, to make a statement, as a sign of belonging to a certain group or class, in everyday design of domestic items and so forth. Even the absence of art carries a meaning. Art unites and it divides people. Art is active; it works on us.
Keywords: taiteellinen työ; taiteilijat; taide; luovuus; taidefilosofia; taideteokset; taiteilijuus; ajattelu; nykytaide; taiteellinen tutkimus